2022
DOI: 10.1007/s00348-022-03420-x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous temperature and thickness measurements of falling liquid films by laser-induced fluorescence

Abstract: Thin wavy liquid films are used in many applications as heat and mass transfer promoters thanks to their great performances for a small liquid consumption. To evaluate the influence of the coupling between the wavy fluid dynamics and the heat transfer in a 2D waves regime, a pointwise laser-induced fluorescence technique has been developed. The technique enables a simultaneous measurement of both the thickness and the temperature of a wavy film flowing down an inclined plane with a high temporal resolution tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Experimental studies also reported the appearance of complex phase-change mechanisms when condensing [17] water vapor or during boiling [22,23] of the falling films in soprtion systems. Despite a very strong interest in understanding the inner workings of heat and mass transfer in falling liquid films by the community, either theoretically [24,25,26,27] or experimentally [28,29,30,31], the literature concerning the component scale of the sorption systems remains scarce and further knowledge on the behaviour of the flows inside of falling films exchanger is required.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies also reported the appearance of complex phase-change mechanisms when condensing [17] water vapor or during boiling [22,23] of the falling films in soprtion systems. Despite a very strong interest in understanding the inner workings of heat and mass transfer in falling liquid films by the community, either theoretically [24,25,26,27] or experimentally [28,29,30,31], the literature concerning the component scale of the sorption systems remains scarce and further knowledge on the behaviour of the flows inside of falling films exchanger is required.…”
Section: Introductionmentioning
confidence: 99%